Suppression of inflammation in ulcerative colitis by interferon-β-1a is accompanied by inhibition of IL-13 production. Issue 4 (22nd October 2010) - Mannon, Peter J; Hornung, Ronald L; Yang, Zhiqiong; Yi, Chuli; Groden, Catherine; Friend, Julia; Yao, Michael; Strober, Warren; Fuss, Ivan J
Abstract : Objective: Ulcerative colitis is associated with increased interleukin 13 (IL-13) production by natural killer T cells. Taking advantage of the inhibitory actions of interferon β on IL-13 expression, this proof-of-concept study aimed to show that decreasing IL-13 production is associated with clinical improvement of ulcerative colitis symptoms. Design: Open-label interventional drug trial. Setting: Outpatient clinical research hospital. Patients: Adult patients with active ulcerative colitis (Short Clinical Colitis Activity Index (SCCAI)≥5). Interventions: Treatment with 30 μg IM interferon-β-1a (Avonex) weekly for 12 weeks with 6 month follow-up. Main outcome measures: Clinical response was defined as ≥3 point drop in the SCCAI for at least two consecutive monitoring visits, and cytokine production was measured in cultured peripheral blood and lamina propria mononuclear cells (LPMC) before and after treatment. Results: 11 of 16 patients were clinical responders, and 4 were in remission (SCCAI ≤ 2) at the end of treatment. Rectal bleeding subscores improved dramatically by week 4 (38% with frank bleeding vs 87% pretreatment). Increased IL-13 production by LPMC T cells fell significantly in clinical responders (690±99 vs 297±58 pg/ml p=0.015) but was unchanged in non-responders (542±83 vs 510±39 pg/ml). In addition, non-responders had significantly higher production of IL-17 and IL-6 pre-treatment compared to responders. Conclusions: Interferon-β-1a induces clinical response and remission in a large subset of patients with ulcerative colitis that is associated with significant inhibition of IL-13 production. In addition, increased IL-17 and IL-6 production is associated with no response to interferon-β. These data provide a proof-of-concept that IL-13 is an effector cytokine in ulcerative colitis and should be a target for novel therapies.